2019
DOI: 10.7554/elife.44674
|View full text |Cite
|
Sign up to set email alerts
|

NHR-14 loss of function couples intestinal iron uptake with innate immunity in C. elegans through PQM-1 signaling

Abstract: Iron is essential for survival of most organisms. All organisms have thus developed mechanisms to sense, acquire and sequester iron. In C. elegans, iron uptake and sequestration are regulated by HIF-1. We previously showed that hif-1 mutants are developmentally delayed when grown under iron limitation. Here we identify nhr-14, encoding a nuclear receptor, in a screen conducted for mutations that rescue the developmental delay of hif-1 mutants under iron limitation. nhr-14 loss upregulates the intestinal metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 87 publications
4
24
1
Order By: Relevance
“…While ftn-1 was previously shown to be upregulated upon DAF-2 inactivation, in a DAF-16 dependent manner, ftn-2 is not considered a DAF-16 target 36 . Also, in agreement with their differential regulation in innate immunity, the expression of ftn-1, but not ftn-2, was reported to depend on PQM-1 28 . Confirming our RNA profiling data by RT-qPCR, and consistent with the regulation by both DAF-16 and PQM-1, we observed a DAF-16 and PQM-1 dependent increase in the levels of ftn-1 mRNA in cold-treated ets-4(-) mutants ( Fig.…”
Section: Ftn-1/ferritin Promotes Cold Survivalsupporting
confidence: 67%
“…While ftn-1 was previously shown to be upregulated upon DAF-2 inactivation, in a DAF-16 dependent manner, ftn-2 is not considered a DAF-16 target 36 . Also, in agreement with their differential regulation in innate immunity, the expression of ftn-1, but not ftn-2, was reported to depend on PQM-1 28 . Confirming our RNA profiling data by RT-qPCR, and consistent with the regulation by both DAF-16 and PQM-1, we observed a DAF-16 and PQM-1 dependent increase in the levels of ftn-1 mRNA in cold-treated ets-4(-) mutants ( Fig.…”
Section: Ftn-1/ferritin Promotes Cold Survivalsupporting
confidence: 67%
“…To identify the potential immune pathways that may play a role in the pathogen resistance to the UNC-30-deficient animals, we performed a gene enrichment analysis using the immune gene subset by employing the Worm Exp tool (https://wormexp.zoologie.uni-kiel.de/wormexp/) (Yang et al, 2016), which integrates all published expression datasets for C. elegans to analyze and generate pathways. We found that pathways required for C. elegans defense against bacterial infections were highly enriched, including the GATA/ELT-2, p38/PMK-1 MAPK, PQM-1, and DAF-2/DAF-16 insulin pathways (Figure 2B and Table S3) (Aballay et al, 2003; Garsin et al, 2003; Head et al, 2017; Huffman et al, 2004; Kerry et al, 2006; Kim et al, 2002; Murphy et al, 2003; Rajan et al, 2019; Shapira et al, 2006; Singh and Aballay, 2006, 2009; Troemel et al, 2006). We also noticed that several of the p38/PMK-1 and FOXO/DAF-16-dependent genes were also controlled by GATA/ELT-2 (Figure S6 and Tables S3), indicating that GATA/ELT-2-dependent genes may play a major role in the enhanced resistance to pathogen phenotype of unc-30(ok613) animals.…”
Section: Resultsmentioning
confidence: 99%
“…elegans to analyze and generate pathways. We found that pathways required for C. elegans defense against bacterial infections were highly enriched, including the GATA/ELT-2, p38/PMK-1 MAPK, PQM-1, and DAF-2/DAF-16 insulin pathways ( Figure 2B and Table S3) (Aballay et al, 2003;Garsin et al, 2003;Head et al, 2017;Huffman et al, 2004;Kerry et al, 2006;Kim et al, 2002;Murphy et al, 2003;Rajan et al, 2019;Shapira et al, 2006;Aballay, 2006, 2009;Troemel et al, 2006). We also noticed that several of the p38/PMK-1 and FOXO/DAF-16-dependent genes were also controlled by GATA/ELT-2 ( Figure S6 and Tables S3), indicating that GATA/ELT-2-dependent genes may play a major role in the enhanced resistance to pathogen phenotype of unc-30(ok613) animals.…”
Section: Pitx/unc-30 Inhibits the Expression Of Immune And Age-relatementioning
confidence: 97%
“…In addition, the C. elegans homolog of the liver X receptor (LXR), NHR-8, which controls cholesterol and bile acid homeostasis, is required for defense against infection with P. aeruginosa [27,28]. Finally, the nuclear hormone receptor NHR-14 links iron availability with the induction of innate immune defenses that provide protection from pathogen infection [29].…”
Section: Transcriptional Control Of Innate Immunity and Metabolism Bymentioning
confidence: 99%
“…aeruginosa [ 27 , 28 ]. Finally, the nuclear hormone receptor NHR-14 links iron availability with the induction of innate immune defenses that provide protection from pathogen infection [ 29 ].…”
Section: Transcriptional Control Of Innate Immunity and Metabolism Bymentioning
confidence: 99%